Character education content in science textbook for senior high school students - Limiansi, Kintan; Suranto, Suranto; Paidi, Paidi; Zuchdi, Darmiyati (International Journal of Evaluation and Research in Education (IJERE), 2025)
Student textbooks need to contain character education following curriculum objectives. This study aimed to describe the character content in high school science textbooks 10th-grade, analyze the distribution of character content on each topic, and identify similarities in each textbook. The research objectives were answered by inferential content analysis. The books analyzed were two textbooks (one published by the government and one published by a private company). The results showed that both textbooks contained dimensions of the Pancasila student profile presented explicitly and implicitly. The analysis showed that the character content in book 1 was 262 and in book 2 was 463. Book 1 is dominated by critical reasoning (39%) and book 2 is dominated by independence (34%). The distribution of characters on each topic in the two books is different, but both books contain all dimensions of the character profile of Pancasila students. The results of this study are considered for teachers to use various books and learning resources in learning. In addition, the results of this study also provide initial information for future researchers to develop a mechanism for measuring the profile of Pancasila students as a feature of the Independent Curriculum.